ASAS-SSR Triennial Reproduction Symposium: The use of natural cycle’s follicular dynamic to improve oocyte quality in dairy cows and heifers(,) - Sirard, Marc André (J Anim Sci, 2018)
The selection of the best dairy heifers is mainly driven by the genetic value of their parents. The phenotype analysis of cows and of the daughters of bulls has been used to identify the best genetic value for decades before being replaced by genomic selection of individuals that are not yet parents. Because it is possible to predict the future value of an individual by its genetic makeup, it becomes feasible to do it as early as the blastocyst stage and to decide which should be transferred or not. Because we know the genotype of an animal at birth, or even before, it is becoming desirable to reproduce this animal as soon as possible to reduce generation interval and improve selection speed. Nature provides constraints that can be overcome: a single oocyte per cycle and age at puberty. Indeed, it is now possible to super-stimulate the ovary at any age and to start collecting oocytes at 6 mo by trans-vaginal ultrasonography. The challenge becomes the production of good eggs and embryos capable of implanting and developing into healthy calves. Our understanding of ovarian follicular physiology has been instrumental in designing stimulation protocols that may be adjusted to any physiological context including age, and even the individual animal, to obtain a good response. Therefore, the combination of procedures developed in cows to optimize oocyte quality, for example, FSH coasting, in association with in vitro fertilization and optimal culture conditions can now result in the production of several female embryos twice a month from animals 6 to12 mo of age. The transcriptomic and epigenetic analyses of embryos produced from the same females at different ages were compared and few differences were noted in particular in relation to embryo metabolism. These embryos are as good as the ones obtained from adult animals and can be produced with sexed sperm of bulls 12 mo of age. This combination of these technical optimizations with blastocyst genotyping allows the selection of a second generation within a year.